Relationship between the learning gains and learning style preferences among students from the school of medicine and health sciences - Blanca Bazán-Perkins; José Alfredo Santibañez-Salgado (BMC Medical Education)
Abstract Background The field of health sciences is constantly evolving, presenting significant challenges to student learning performance. Therefore, it is crucial to identify the factors influencing students' learning style preferences, as these relate to how they acquire, understand, interpret, organize, and process information from their courses. In this study, we evaluated whether there is a relationship between students' learning style preferences and their learning gains. Methods A cross-sectional study was conducted between 2021 and 2022 using a convenience sampling approach with students of the School of Medicine and Health Sciences at the Mexico City Campus of Tecnológico de Monterrey. Students completed online questionnaires to assess normalized learning gains, as well as preference questionnaires from the VARK inventory (Visual, Auditory, Reading/Writing, and Kinesthetic types of learning preferences) and the Felder-Silverman learning style model, which is a framework that categorizes learners based on their preferences across several dimensions: active/reflective, sensing/intuitive, visual/verbal, and sequential/global. Descriptive statistics and Spearman’s correlation were used to analyze the data. Results In relation to the VARK inventory, students exhibited a tendency to prefer multimodal sensory learning, particularly favoring the kinesthetic style. The number of VARK styles and the preference for kinesthetic learning were significantly correlated with learning gains. The Felder-Silverman test indicated that students preferred sensing, visual, and sequential learning; however, the levels of preference for active, intuitive, and sequential learning were associated with higher learning gains. Reflective learning demonstrated an inverse correlation with learning gains. Conclusion Our results indicate the importance of incorporating experience and practical skills in the classroom. Additionally, it is recommended that students work collaboratively, share and discuss learning materials, foster innovation and abstract learning, and follow logical and sequential approaches to optimize their educational achievements. It is fundamental to find learning models that improve the academic performance of students with a reflective learning preference.